2005
DOI: 10.1007/s10526-004-1295-1
|View full text |Cite
|
Sign up to set email alerts
|

Response of Trichogramma chilonis to infochemicals: an SEM and electrophysiological investigation

Abstract: The external morphology and peripheral olfactory responses of antennal chemoreceptors of Trichogramma chilonis Ishii (Hymenoptera:Trichogrammatidae) to host related stimuli were examined by SEM and EAG technique respectively. The antennae of male and female T. chilonis reveal strong sexual dimorphism in structure as well as in types, density and distribution of individual sensillar types. The female antennae are characterized by the presence of a single uniporous sensilla on the apical tip of the dome and nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…3.6f, g). Sen et al (2005) discussed a similar hypothesis for this sensillum in Trichogramma chilonis (Ishii) females.…”
Section: Uniporous Sensillamentioning
confidence: 74%
See 1 more Smart Citation
“…3.6f, g). Sen et al (2005) discussed a similar hypothesis for this sensillum in Trichogramma chilonis (Ishii) females.…”
Section: Uniporous Sensillamentioning
confidence: 74%
“…These sensilla are laterally flattened, ending with a sharp tip and they show numerous grooves running parallel on both sides up to the ventral margin, where they converge. For these sensilla, different functional hypothesis have been proposed; from bi-modal mechano-chemosensory units (Voegelé et al 1975) to olfactory organs (Sen et al 2005). TEM investigations on T. brassicae (Isidoro et al 1996) revealed the following ultrastructural features: (i) a multiporous area located along the ventral margin (Fig.…”
Section: Multiporous Gustatory Sensillamentioning
confidence: 99%
“…No corrections were made for differences in volatility between the test compounds. Consequently, comparisons among responses were relative (Sen et al 2005). The threshold of response to each compound was taken as the minimum stimulus concentration at which, relative to the standard, the EAG percent to the stimulus was significantly greater (P = 0.05) than that to the corresponding solvent controls.…”
Section: Odors Stimulimentioning
confidence: 99%
“…In parasitic or predatory insects, there is a conspicuous sexual dimorphism in antennal sensillary structures, probably functioning in identifi cation of ovipositional substrates in females and as mate locating organs in males. Sen et al ( 2005 ) studied the external morphology and peripheral olfactory responses of antennal chemoreceptors of the generalist parasitoid Trichogramma chilonis to host plant-related chemical stimuli using scanning electron microscope (SEM) and EAG techniques. Uniporous sensilla on the antennal tip and numerous multiporous pitted sensilla character-ise the female antennae.…”
Section: Sensory Organs and Plant Chemical Perceptionmentioning
confidence: 99%